2020
DOI: 10.1080/23311932.2020.1773690
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing irrigation frequency and amount on yield and water productivity of snap bean (Phaseolus Vulgaris L.) in NW Amhara, Ethiopia: A case study in Koga and Ribb irrigation scheme

Abstract: This study has investigated the effects of different irrigation frequency and depth on yield and water productivity of snap bean at Koga and Ribb irrigation scheme, NW Amhara, Ethiopia. It was done in a factorial experiment laid out in split-plot design with three replications of two irrigation intervals and five variable irrigation depths. Irrigation depth had shown a significant effect on marketable pod yield, and irrigation water productivity whereas irrigation frequency hadn't shown a significant effect. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…The harmful effects of water deficit on grain yield were also reported in several other studies [82,[93][94][95][96][97][98], where reduced irrigation also lowered yield and yield components. Additionally, limited water availability (i.e., soil moisture levels) due to high levels of evaporation also negatively impacts yield components [10], fresh pod [7,9] or grain yields [8,99]. The detrimental effects of prolonged water deficit stress were also recorded in the studies of Dapaah et al [100,101] and Love et al [102], where common bean plants were exposed to no irrigation during the whole cultivation period.…”
Section: Irrigationmentioning
confidence: 96%
See 1 more Smart Citation
“…The harmful effects of water deficit on grain yield were also reported in several other studies [82,[93][94][95][96][97][98], where reduced irrigation also lowered yield and yield components. Additionally, limited water availability (i.e., soil moisture levels) due to high levels of evaporation also negatively impacts yield components [10], fresh pod [7,9] or grain yields [8,99]. The detrimental effects of prolonged water deficit stress were also recorded in the studies of Dapaah et al [100,101] and Love et al [102], where common bean plants were exposed to no irrigation during the whole cultivation period.…”
Section: Irrigationmentioning
confidence: 96%
“…Moreover, reduced tillage demands a drastic decrease in the use and size of farm machinery and fuel, with consequent reduction in Greenhouse Gas (GHG) Emissions and management costs [6]. Irrigation management, especially during flowering or reproduction, is also crucial for crop productivity and quality in most parts of the world [7][8][9][10]. Introduction of high yielding cultivars with superior product qualities and increased tolerance to biotic and abiotic stresses, as well as application or/and encouragement of beneficial microorganisms (e.g., bacteria, algae, fungi) with the potential to increase nutrient and water uptake without compromising environment functions should also be considered as viable sustainable agronomic practices to improve plant performance and productivity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[46], which discovered that the maximum green bean pod lengths were produced at 100% ETc at ten-day irrigation intervals, the length of pods in this site is low in contrast to the Rift Valley region of Ethiopia, which varies between 10.6 and 12.8 cm [13 as cited by Ref. [46]].…”
Section: Pod Lengthmentioning
confidence: 99%
“…Additionally, cotton water productivity was evaluated using different amounts of irrigation water and different drip irrigation techniques (surface drip irrigation and subsurface drip irrigation) [ 16 ]. Abebe et al showed that irrigation depth had significant effects on the marketable yield and water productivity of broad beans ( Vicia faba L.), whereas irrigation frequency had no significant effects on the marketable yield of broad beans [ 17 ].…”
Section: Introductionmentioning
confidence: 99%